TraceTogether contact tracing: a Smart Nation innovation - Hansen, Michael Motet; Dahiya, Bharat (Frontiers in Sustainable Cities, 2025)
As urban populations grow, cities increasingly turn to smart city initiatives to enhance efficiency, citizen well-being, and economic development. Singapore’s Smart Nation strategy exemplifies this trend by leveraging technology and citizen inclusion. This study investigates the key success factors of Singapore’s smart city model, focusing on the TraceTogether app used during the COVID-19 pandemic. The research employs a mixed-methods approach, including a comprehensive literature review, conceptual framework development, and an in-depth case study of the TraceTogether application. Primary data was collected through semi-structured interviews with stakeholders such as policymakers, technology developers, and citizens and an analysis of digital platforms and feedback mechanisms. Findings show that Singapore’s Smart Nation initiative succeeded due to strong governance, citizen trust, strategic technological implementation, and active public participation. The TraceTogether app showcased effective public health surveillance through a privacy-conscious, Bluetooth-based system. Citizen feedback was integrated via social media, interviews, and engagement programs like Smart Nation Ambassadors. The study underscores the importance of inclusive governance, cross-sector collaboration, and digital literacy in successfully implementing smart city technologies. While the TraceTogether app demonstrated efficient crisis response, challenges remain regarding data privacy, digital divide, and long-term scalability. The research offers insights for cities aiming to replicate Singapore’s model by prioritizing citizen-centric design and adaptive policy frameworks.